Correlation Between Parts Readiness and On Time In Full (OTIF) Performance - Rahil Najmul Bahiyyah; Firda Ainun Nisah (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
PT XYZ is a distributor company that moves in the heavy equipment sector. One of KPIs that is used to evaluate the company’s operations is On Time In Full (OTIF). On the other side, PT XYZ is monitoring the readiness of spare parts in all branches on a daily basis. The objective of this research is to find out if there is a correlation between spare parts readiness and OTIF performance, to identify to what extent the readiness of parts can affect OTIF performance, and to provide a solid understanding basis for companies to make strategic decisions related to improve company processes and achieve optimal OTIF performances. The method that will be performed in this article is Pearson correlation, by using historical data from the 5 branches (Jakarta, Medan, Banjarmasin, Ujung Pandang, and Sorong). From the research, it is known that the correlation values in the 5 branches are, by order, 50%, 49%, 55%, 56%, 58% in which all of them are categorized as “moderate positive”, which means between parts readiness and OTIF performance in the company is correlated, but it can also be affected by other factors such as lead time agreement, strategic inventory management, solid cooperation between company branches, and a good relationship between company and the principal.